PENGARUH JEJARI HIDROLIK REGENERATOR DAN FREKUENSI GELOMBANG BUNYI TERHADAP KINERJA POMPA KALOR TERMOAKUSTIK GELOMBANG BERJALAN - Prastowo Murti; Ikhsan Setiawan; Muhammad Fadly; Solli Dwi Murtyas (Jurnal Teknologi, 2018)
The refrigerant in the conventional heat pump has affected to the environmental. One of them is ozone depletion, thus, heat pump which has no impact on the environment is needed. The thermoacoustic heat pump is heat pump device which employs thermoacoustic phenomena and works with no refrigerant hence environmental benign. Thermoacoustics is phenomena sound wave that can cause a temperature difference or vice versa. The thermoacoustic heat pump produces temperature difference in the both side of the regenerator in which can be used as refrigerator and heater. Thermoacoustic heat pump consists of resonator tube, loudspeaker, and regenerator. Regenerator is the heart of thermoacoustic which is energy conversion takes place. Therefore, this research focuses on optimization of hydraulic radius of stainless steel wire mesh regenerator and frequency of the sound wave on the performance traveling-wave thermoacoustic heat pump. The experimental results show that hydraulic radius of regenerator and frequency of sound wave gives significant effect to temperature difference on the both side of the regenerator. The largest temperature difference reach is 51,5 °C, which is cold side have 12,2 °C that can be used as a refrigerator and hot side have 63,6 °C that can be used as a heater.